Shaping colloidal bananas to reveal biaxial, splay-bend nematic and smectic phases - Fernandez-Rico, C; Massimiliano, C; Yanagishima, T; de Sousa, H; Aarts, DGAL; Dijkstra, M; Dullens, RPA (American Association for the Advancement of Science, 2020)
Understanding the impact of curvature on the self-assembly of elongated microscopic building blocks, such as molecules and proteins, is key to engineering functional materials with predesigned structure. We develop model “banana-shaped” colloidal particles with tunable dimensions and curvature, whose structure and dynamics are accessible at the particle level. By heating initially straight rods made of SU-8 photoresist, we induce a controllable shape deformation that causes the rods to buckle into banana-shaped particles. We elucidate the phase behavior of differently curved colloidal bananas using confocal microscopy. Although highly curved bananas only form isotropic phases, less curved bananas exhibit very rich phase behavior, including biaxial nematic phases, polar and antipolar smectic-like phases, and even the long-predicted, elusive splay-bend nematic phase.